Unwind - "Burns, Robert B" (Crows Nest, 2004)
Work deadlines. Peak hour traffic. Exams. Home and work life in the 21st Century is hectic, demanding and, at times, increasingly stressful. Often stress is the result of having to cope with today's fast-changing, competitive and time-pressured world.However, stress can be beneficial as well. Think of the adrenaline rush of meeting a deadline or the relief of finishing your exams. You might not be able to eliminate stress from your life, but you can ensure that you are functioning at your optimum stress levels.Here are ten simple skills to help you identify and manage stress in your life - both at home and at work - to improve your wellbeing and get you functioning at your very best. These skills are easy to learn, and there are activities to assist you along the way.Don't let stress control your life; harness your stress to perform at your peak and then learn to let it go, relax and unwind.
Keywords: Stress management